2019
DOI: 10.1007/978-3-030-29390-1_20
|View full text |Cite
|
Sign up to set email alerts
|

Design and Evaluation of an Augmented Reality App for Learning Geometric Shapes in 3D

Abstract: Augmented Reality (AR) is increasingly used as an educational tool in a range of domains with the goal of enhancing students' performance as well as their learning experience, thanks to the interactivity and visual appeal of AR objects. While some attempts, albeit limited, have been undertaken to prove these beneficial effects in learning 3D geometry, the results remain inconclusive and there are some methodological issues such as under-evaluation of user experience. With the aim to enrich the applied body of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…In mathematics education, AR has a big potential and opportunities for students to learn and interact with three-dimensional models in the real world. The usage of AR in mathematics education has increased especially in geometry and other complex concepts (Liu et al, 2019;Thamrongrat & Law, 2019). In these studies, it is reported that the use of AR has a positive effect on students' learning performance and attitude toward mathematics, especially in classes that focus on solid geometry and more abstract geometric concepts.…”
Section: Introductionmentioning
confidence: 99%
“…In mathematics education, AR has a big potential and opportunities for students to learn and interact with three-dimensional models in the real world. The usage of AR in mathematics education has increased especially in geometry and other complex concepts (Liu et al, 2019;Thamrongrat & Law, 2019). In these studies, it is reported that the use of AR has a positive effect on students' learning performance and attitude toward mathematics, especially in classes that focus on solid geometry and more abstract geometric concepts.…”
Section: Introductionmentioning
confidence: 99%
“…In mathematics, and particularly in geometry, spatial visualizations are essential. Spatial-visual intelligence, as defined by Thamrongrat (2021), can be characterized as the ability to see the world accurately and to change those perceptions. In mathematics, and particularly in geometry, spatial visualizations are essential.…”
Section: Introductionmentioning
confidence: 99%
“…AR technologies have positive potential advantages that can be adapted in education (Saidin et al, 2015). In mathematics education, some studies report that AR has positive effect on students' learning performance and attitude in mathematics, especially in solid geometry class (Liu et al, 2019) and for the more complex geometric concepts (Thamrongrat & Law, 2019). This potential can be exploited for improving students' engagement and quality of mathematics learning.…”
mentioning
confidence: 99%